Negotiations among traditional leaders in Muna tribal marriages - Marsaban, Al; Said, Taufiq (Yayasan Irwan Abdullah Cendekia, 2023)
In Muna community marriage is known as kawin pinang and kawin lari. Elopement is done as a way out or solution for the Muna community. Negotiation is crucial in this research because, in the literature review conducted by the author, as many as 25 national journals did not discuss in depth about negotiations in marriage. This research was analyzed using a descriptive qualitative method with data collection techniques of in-depth interviews and participatory observation. The results of this study show that in the marriage process for the Muna community, starting from finding a mate, proposing, and ending with a marriage, the role of traditional leaders is needed. Traditional leaders who function as mediators and facilitators through negotiations or deliberations can influence the value of the dowry itself